Pemanfaatan Pelayanan Kesehatan Imunisasi Dasar Berdasarkan Kepemilikan Buku Kia Di Jawa Timur (Riskesdas 2018) - Lulus Prihandari; Dumilah Ayuningtyas (Ridwan Institute, 2021)
The maternal and child health book is important in conveying information related to maternal and child health, especially covering basic immunization for infants. The use of maternal and child health books is still not optimal, as evidenced by the data on the coverage of kia book ownership in east java province, around 1.7% do not have kia books. The purpose of this study was to analyze the relationship between ownership of the mch handbook which includes recording, education and communication with the use of basic immunization health services. This study used a quantitative descriptive research method, which was conducted in the period october-december 2020, using secondary data from riskesdas 2018. Data analysis included univariate by conducting frequency distribution tests and bivariate analysis with logistic regression tests. The results of the mch book ownership obtained a statistical analysis of p value = 0.245 (p> 0.05), it can be concluded that there is no significant relationship between mch book ownership and the use of basic immunization health services.